Pertanggungjawaban Hukum Anak Dalam Pelaku Tindak Pidana Berat: Pendekatan, Dampak, Dan Implikasi Dalam Sistem Peradilan Anak - Anik Iftitah; Eko Yuliastuti; Desy Okta Mawarni; Rila Puspita Wardani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This study discusses the legal responsibility of children against perpetrators of serious crimes. The question of the extent to which children can be held accountable for their criminal acts has been controversial in the juvenile justice system. Some countries apply a strict legal system, where children can be subject to the same sanctions as adults, while other countries adopt a rehabilitation and reintegration approach. The impact of the approach applied to the legal responsibility of children as perpetrators of serious crimes can affect the future of these children. An approach that focuses on rehabilitation and reintegration provides opportunities for children to find recovery and a second chance in society. However, an approach that promotes punishment can potentially harm children and hinder their rehabilitation process. In this context, it is necessary to have a balanced and comprehensive approach in treating children as perpetrators of serious crimes. Protection of children's rights, moral development and an approach that is based on the best interests of the child must be the cornerstone of the juvenile justice system.